Control of pH and PIP2 gating in heteromeric Kir4.1/Kir5.1 channels by H-Bonding at the helix-bundle crossing. - Rapedius, M; Paynter, J; Fowler, P; Shang, L; Sansom, MS; Tucker, S; Baukrowitz, T (2007)
Inhibition by intracellular H(+) (pH gating) and activation by phosphoinositides such as PIP(2) (PIP(2)-gating) are key regulatory mechanisms in the physiology of inwardly-rectifying potassium (Kir) channels. Our recent findings suggest that PIP(2) gating and pH gating are controlled by an intra-subunit H-bond at the helix-bundle crossing between a lysine in TM1 and a backbone carbonyl group in TM2. This interaction only occurs in the closed state and channel opening requires this H-bond to be broken, thereby influencing the kinetics of PIP(2) and pH gating in Kir channels. In this addendum, we explore the role of H-bonding in heteromeric Kir4.1/Kir5.1 channels. Kir5.1 subunits do not possess a TM1 lysine. However, homology modelling and molecular dynamics simulations demonstrate that the TM1 lysine in Kir4.1 is capable of H-bonding at the helix-bundle crossing. Consistent with this, the rates of pH and PIP2 gating in Kir4.1/Kir5.1 channels (two H-bonds) were intermediate between those of wild-type homomeric Kir4.1 (four H-bonds) and Kir4.1(K67M) channels (no H-bonds) suggesting that the number of H-bonds in the tetrameric channel complex determines the gating kinetics. Furthermore, in heteromeric Kir4.1(K67M)/Kir5.1 channels, where the two remaining H-bonds are disrupted, we found that the gating kinetics were similar to Kir4.1(K67M) homomeric channels despite the fact that these two channels differ considerably in their PIP(2) affinities. This indicates that Kir channel PIP(2) affinity has little impact on either the PIP(2) or pH gating kinetics.